Meningkatkan Literasi dan Numerasi dengan Memadukan Teknologi pada Program Kampus Mengajar 6 di SD N 2 Tamansari - Safitri, Arisanti Dwi; Yunita, Ika Romadoni; Ajeng Widiawati, Chyntia Raras (Universitas Pahlawan Tuanku Tambusai, 2024)
The Teaching Campus is an MBKM (Free Learning Campus) program organized by the Ministry of Education and Culture with the aim of providing opportunities for students to learn and develop themselves through activities outside of lectures. This program gives students the opportunity to become teacher partners, encourage learning innovation, and develop literacy, numeracy, and technology adaptation in the 3T area. Focus is also given to efforts to increase people's interest in reading and the importance of literacy and numeracy, including the obstacles faced in its implementation. This research aims to revive the school literacy movement through literacy and numeracy familiarization activities. The research results show that technical training, understanding material concepts, and introducing technology are the main focuses of mentoring. The implementation of the Literacy and Numeracy Minimum Competency Assessment (AKM) with technological devices provides positive results, including increasing understanding of numeracy material, individual development, motivation and self-confidence of students. This research provides a positive picture of the potential for improving the quality of basic education through the Teaching Campus program.